LOXOSCELISM IN A CANINE: CASE REPORT - Santana, Bruno Borges; de Souza, Lucas Cinquini Cesquim; Tayar, Kamilla Souza; Amaral, Indyara Natylla Castro; Zuin, Isabela Orsi; Paschoal, Laís Campoi; Garcia, Victoria Talarico; de Freitas, Katriny Pereira; de Rezende, Rodrigo Supranzetti (Seven Editora, 2025)
The brown recluse spider, of the genus Loxosceles, is an arachnid with non-aggressive behavior that bites only when pressed against the body. Its bite can cause cutaneous clinical manifestations, with slow-healing dermonecrotic lesions, or cutaneous-visceral effects, including acute renal failure due to the nephrotoxic action of the venom. This study reports the case of a six-year-old female Pinscher treated at the Animais e Cia Veterinary Hospital in Uberaba (MG). The patient presented ulcerated wounds on the right thoracic limb, consistent with clinical signs of loxoscelism. The diagnosis was established based on history, lesion characteristics, and exclusion of other conditions. Treatment included topical dressings, antibiotics, analgesics, anti-inflammatory drugs, and symptomatic support, resulting in complete lesion healing after 21 days. This case highlights the importance of early recognition of clinical signs and appropriate therapy to prevent complications and achieve a favorable prognosis.DOI: https://doi.org/10.56238/sevened2025.029-013